STRATEGI KPU KOTA SUKABUMI DALAM MENINGKATKAN ANGKA PEMILIH RASIONAL PADA PEMILU SERENTAK TAHUN 2024 - Dian Purwanti; M. Syahril Nazwa; Laila Nur Redha Putri; Ranti Rahmawati (Jurnal Kebijakan Pembangunan Daerah, 2024)
This study is motivated by the lack of understanding and awareness among the people of Sukabumi City regarding the importance of being rational voters. Based on the 2019 local election, it was found that 9% of voters in Sukabumi City were still pragmatic. The type of research used in this study is qualitative research with a descriptive approach. The aim of this study is to identify the strategies employed by the Sukabumi City Election Commission (KPU) to increase the number of rational voters in the 2024 elections in Sukabumi City. The data and information required for this study were obtained from informants using two types of data, namely primary and secondary data. The data collection technique used in this study is snowball sampling. This study employs Geoff Mulgan's theory, which consists of three dimensions: Purpose, Action, and Environment. The results show that the purpose of the socialization strategy by the Sukabumi City Election Commission is to raise the awareness of the people of Sukabumi City about the importance of being rational, intelligent, and high-quality voters. The actions taken by the Sukabumi City Election Commission include providing counseling on the importance of voting, understanding candidates and their platforms, and proper voting procedures. This includes voter education for first-time voters and distributing flyers to the people of Sukabumi City through various programs like Sapa Warga, public discussions, social media campaigns, and the distribution of voter education materials. The environment of the socialization strategy implemented by the Sukabumi City Election Commission is reviewed from several aspects of community behavior based on economic, social, and cultural aspects. Essentially, the environment and community behavior will influence the voter categories themselves.